Efek variasi suhu dan waktu blanching pada kualitas manisan nangka kering (Artocarpus heterophyllus) - Lorine Tantalu; Sri Handayani; Rozana Rozana; Ferianus Wunga (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
The aim of this study was to obtain a combination of blanching temperature and time in making candied jackfruit. Randomized factorial was used as research design within two factors, namely blanching temperature (80oC, 85oC, and 90oC) and blanching time (2, 3, and 4 minutes). The quality test of candied dried jackfruit includes organoleptic test of the hedonic scale scoring method namely taste, color, aroma, and texture. Chemical tests include water content, sugar content, and yield. The best treatment is a combination of 90oC blanching temperature and 4 minutes blanching time, which produces a product with a water content of 40.91%, a sugar content of 73.72%, even for yield raised up to 35.51%. Taste, color, aroma, and texture parameters did not show any real effect. Based on the results of the business feasibility analysis, it is found that the processing of the candied jackfruit processing industry is feasible to be cultivated on a small industrial scale.